Espaços que insistem, vidas que resistem : a longa permanência em questão - Louzada, Williana Nunes de Moraes (2012)
Between wires, stones and needles, this paper is done sewing, weaving, plotting stories, concepts and lives. From the interpolations of the field, a research is open through the Psychiatric Reform underway in the city of Niterói. An encounter with the clinic that dares to propose axes to think the specificities of care in the long-stays of psychiatric hospitals and the effects of institutionalization today. Immersed in a in hospital living space, called the Long, in the Jurujuba Psychiatric Hospital - Niterói, RJ, we used the principle of losing time to gain life. Constructions of heterotopies as an Outside that goes tacking on deinstitutionalization. We bring the story of Emeralds, Pearls and Daisies as the force that has been able to build itself, but with the marking of an inside that still insists